IMPROVING STUDENTS’ MOTIVATION AND LEARNING OUTCOMES WITH SCIENTIFIC LEARNING APPROACH - Kamil, Firmanilah (Jurnal Tatsqif, 2023)
With the decrease in COVID-19 cases in Indonesia, learning activities are expected to return to normal in the new academic year 2022/2023. To increase the interest and motivation of civil engineering students, a student-centered approach is needed in theory-practicum learning. Scientific learning approach was implemented to increase students’ motivation and learning outcomes of Civil Engineering students after the Covid-19 Pandemic. This study is class action research conducted at Politeknik Negeri Ketapang with 29 samples. The scores of learning interest, learning motivation, and learning outcomes were analyzed by comparing student scores with the KKM (Minimum Completeness Criteria) score and making a percentage of class completeness. In cycle I, the completeness of student motivation and interest in learning was still less than 50%, so it was continued to cycle II, and at the end of cycle II, motivation and interest in learning still had not reached 50%, then the cycle was continued. At the end of cycle III, it was found that motivation and interest in learning were 68.97% and 79.31%, respectively. In addition to motivation and interest in learning, researcher also compared it with student learning outcomes in each cycle. It was found that, on average, the number of students who completed the percentage of completeness and the minimum and maximum scores for student learning outcomes also increased in each cycle. So, it can be concluded that the scientific approach can improve learning motivation and learning outcomes through classroom action research.